Imaging in Pediatric Urinary Tract Infections - Back, Susan J.; Hartung, Erum A.; Ntoulia, Aikaterini; Darge, Kassa (Journal of Pediatric Infectious Diseases, 2017)
Urinary tract infections (UTIs) commonly occur in children, and the clinical presentation varies depending on the child's age. The infection may affect only the bladder or may involve the kidneys and ureters. Multiple imaging modalities may be used to evaluate for underlying anomalies and complications of the infection. Here we discuss current imaging in pediatric UTI.
Keywords: urinary tract infection; pediatric; ultrasound; contrast-enhanced ultrasound; MRI